2016
DOI: 10.1016/j.jaip.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis without Nasal Polyps

Abstract: Chronic rhinosinusitis without nasal polyps (CRSsNP) is more prevalent than chronic rhinosinusitis with nasal polyps (CRSwNP). Certain diseases predispose to whereas others are associated with CRSsNP. Predisposing diseases include allergic and non-allergic upper and lower airway diseases, epithelial cell disorders, immunodeficiencies, autoimmune diseases, and some infectious diseases. Additionally, environmental and host factors, examples of which include smoking, a higher incidence of abnormal biofilms, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 115 publications
(115 reference statements)
4
55
0
1
Order By: Relevance
“…CRS phenotypes can be divided into CRSwNP and CRSsNP based on the presence or absence of nasal polyps via endoscopic findings. Epidemiologic studies across geographic regions indicate CRSsNP is more prevalent in all ages than CRSwNP . However, available topical steroid therapies are only indicated for nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…CRS phenotypes can be divided into CRSwNP and CRSsNP based on the presence or absence of nasal polyps via endoscopic findings. Epidemiologic studies across geographic regions indicate CRSsNP is more prevalent in all ages than CRSwNP . However, available topical steroid therapies are only indicated for nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…11 CRSsNP is characterized mostly by fibrosis and neutrophilic inflammation, as well as by T H 1 or T H 17 responses. 12 CRSwNP (Fig 1) is associated with moderate or severe T H 2 eosinophilic inflammation and comorbid asthma. However, several studies in recent years have suggested that the molecular diversity in CRS pathogenesis is more complex and that this classification might not be sufficient.…”
mentioning
confidence: 99%
“…Individual manuscripts on the theme issue include findings that the presence of polyps raises the specter of CF [4,5] but CRS without polyps raises no pediatric discussion [6]. The authors of the manuscripts about infectious CRS and AERD provided no pediatric perspective [7,8], but children are briefly mentioned in a section of other phenotypes [5].…”
Section: Definitions Of Adult Chronic Rhinosinusitismentioning
confidence: 99%
“…A condition of adult CRS without polyps appears to exist [6]. However, its presence as a distinct pediatric entity is non-existent in the literature.…”
Section: Pediatric Chronic Rhinosinusitis Without Polyps (Pediatrimentioning
confidence: 99%